Pharmacokinetic interaction between fimasartan and atorvastatin in healthy male volunteers - Choi Y; Lee S; Jang IJ; Yu KS (Dove Medical Press, 2018)
Yewon Choi, SeungHwan Lee, In-Jin Jang, Kyung-Sang Yu Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea Introduction: Major cardiovascular risk factors, including hypertension and dyslipidemia, are often comorbidities, frequently leading to concurrent prescription of angiotensin receptor blockers and 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins). The study’s objective was to evaluate the effect of coadministration of fimasartan and atorvastatin on their pharmacokinetics (PKs). Subjects and methods: In a randomized, open-label, three-period, six-sequence, crossover, multiple-dose study, 36 healthy subjects received 120 mg fimasartan, 40 mg atorvastatin, or both (based on their assigned sequence) once daily for 7 days in each period, with a 7-day washout between periods. Blood samples for the PK analysis of fimasartan, atorvastatin, and the 2-hydroxy atorvastatin metabolite were collected up to 48 h after the last dose. Results: The coadministration of fimasartan and atorvastatin was well tolerated and led to an increase in the peak concentration and area under the concentration–time curve at steady state of fimasartan by 2.18-fold (95% confidence interval [CI], 1.79–2.65) and 1.35-fold (95% CI, 1.26–1.43) and those of atorvastatin increased by 1.82-fold (95% CI, 1.51–2.18) and 1.12-fold (95% CI, 1.04–1.22), respectively. Conclusion: Coadministration increased the systemic exposures of fimasartan and atorvastatin, but the clinical significance of this finding needs to be evaluated with respect to exposure responses and clinical outcomes. Keywords: angiotensin receptor blocker, statin, HMG-CoA inhibitor, fixed dose combination, FDC